New record of Pseudocidaris sp. (Echinoidea:Hemicidaridae) of lower Cretaceous (Valanginian-Hauterivian) from Zapatoca, (Santander Colombia). (2015)
In this study it is reported and described a regular echinoderm of Pseudocidaris genus in the Rosablanca Formation of Lower Cretaceous at the municipality of Zapatoca (Santander, Colombia). The species shows little sinuosity in the ambulacra and a dyciclic apical disc. An exploratory phylogenetic analysis showed that the lineage of the Zapatoca species was originated in the Callovian with P. Romani and that it is related with P. lusitanica (Oxfordian) and P. clunifera ( Barremian-Aptian)